2023
DOI: 10.1590/1519-6984.269245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the antibacterial activity of trans-anethole against Enterococcus cloacae and Enterococcus faecalis strains of food origin

Abstract: The present study sought to evaluate the antibacterial activity of trans-anethole against food-borne strains of Enterobacter cloacae and Enterococcus faecalis. The study was performed using Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) methods, in addition, disc diffusion technique was used to evaluate the association of trans-anethole with synthetic antimicrobials. Minimum Inhibitory Concentration for Adherence (MICA) testing was also performed. The results revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Indeed, in a study by Senatore et al [56], a trans-anethole-rich oil from another plant species, i.e., Foeniculum vulgare leaves, exhibited antibacterial activity against a series of bacterial strains, including Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus faecalis, Escherichia coli and Klebsiella pneumoniae, etc., attesting to the potential of anethole to significantly inhibit the growth of several bacteria. Other studies [57][58][59] have also revealed the antibacterial activity of trans-anethole against numerous bacterial strains. Previous studies have also demonstrated the inhibitory effect of E-anethole against some fungal strains, such as Saccharomyces cerevisiae [47]; however, the antibacterial activity of E-anethole has not yet been reported.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, in a study by Senatore et al [56], a trans-anethole-rich oil from another plant species, i.e., Foeniculum vulgare leaves, exhibited antibacterial activity against a series of bacterial strains, including Bacillus subtilis, Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus faecalis, Escherichia coli and Klebsiella pneumoniae, etc., attesting to the potential of anethole to significantly inhibit the growth of several bacteria. Other studies [57][58][59] have also revealed the antibacterial activity of trans-anethole against numerous bacterial strains. Previous studies have also demonstrated the inhibitory effect of E-anethole against some fungal strains, such as Saccharomyces cerevisiae [47]; however, the antibacterial activity of E-anethole has not yet been reported.…”
Section: Discussionmentioning
confidence: 97%